2018
DOI: 10.1038/s41588-018-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput inference of pairwise coalescence times identifies signals of selection and enriched disease heritability

Abstract: Interest in reconstructing demographic histories has motivated the development of methods to estimate locus-specific pairwise coalescence times from whole-genome sequencing data. Here we introduce a powerful new method, ASMC, that can estimate coalescence times using only SNP array data, and is orders of magnitude faster than previous approaches. We applied ASMC to detect recent positive selection in 113,851 phased British samples from the UK Biobank, and detected 12 genome-wide significant signals, including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
163
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(170 citation statements)
references
References 90 publications
(123 reference statements)
7
163
0
Order By: Relevance
“…This finding leads to reconsider the structural and regulatory elements in the entire region as a unit involved in health and disease (Oxelius, 2008;Oxelius & Pandey, 2013). In agreement with this, the region showed signals of recent positive selection (Palamara, Terhorst, Song, & Price, 2018). In this context, adaptation to the local environments (Hancock et al, 2011;Iskow, Gokcumen, & Lee, 2012;Oxelius, 2000) may have been a major drive for divergence.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…This finding leads to reconsider the structural and regulatory elements in the entire region as a unit involved in health and disease (Oxelius, 2008;Oxelius & Pandey, 2013). In agreement with this, the region showed signals of recent positive selection (Palamara, Terhorst, Song, & Price, 2018). In this context, adaptation to the local environments (Hancock et al, 2011;Iskow, Gokcumen, & Lee, 2012;Oxelius, 2000) may have been a major drive for divergence.…”
Section: Introductionmentioning
confidence: 78%
“…As far as recent selection is concerned, Palamara et al () analyzed the UK Biobank data and identified an excess of recent coalescence events in the immunoglobulin complex, which is attributable to positive selection during the past 20,000 years. While this signal is centered telomerically to IGHG3 , the resolution of the method is of the order of megabases and may imply that the genomic region here considered is also involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common 69 strategy for obtaining the full likelihood has been to find the distribution of the genealogy under 70 selection. For example, Krone and Neuhauser described the distribution of the coalescence tree of 71 a locus under weak selection and no recombination [27]. Alternatively, one can describe how the 72 genealogy depends on the trajectory of the selected allele (first described by [28]), and in turn how 73 2/46 the trajectory depends on selection.…”
Section: Introduction 29mentioning
confidence: 99%
“…It may also possible to make use of recent advances in inferring pairwise coalescence times 613 (e.g., [71]) to build an approximation to the full likelihood. Recently, Albers & McVean proposed 614 a composite likelihood method to estimate allele age by "sandwiching" the age using identity-by-615 descent tracts at the site of interest [72].…”
mentioning
confidence: 99%